2020
DOI: 10.1101/2020.01.02.893081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flattening of diurnal glucocorticoid oscillations causes Cd36 and insulin-mediated obesity

Abstract: Chronic stressors flatten circadian glucocorticoid oscillations, which has been correlated with negative health outcomes including obesity. How flatter circadian glucocorticoid oscillations affect metabolism and fat storage remains unknown. Here we aimed to investigate the consequences of flattened glucocorticoid oscillations in mice. We found that flattening glucocorticoid oscillations not only results in body weight gain mainly due to an increase in white fat depot mass, but also leads to fat accumulation in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Transcriptomic analysis of BAT from corticosteronetreated mice revealed increases in genes involved in lipid synthesis and degradation, including Lpin1 (encoding lipin-1, which regulates adipose tissue triglyceride metabolism) and Acsm5 (Acyl-CoA synthetase medium chain family member 5). Corticosterone-mediated flattening of circadian rhythm also induced expression of the lipid uptake receptor CD36, and corticosteroneinduced obesity and lipid accumulation in BAT and VAT were partially abrogated in CD36-null mice (113).…”
Section: Glucocorticoids and Bat Thermogenesismentioning
confidence: 94%
See 1 more Smart Citation
“…Transcriptomic analysis of BAT from corticosteronetreated mice revealed increases in genes involved in lipid synthesis and degradation, including Lpin1 (encoding lipin-1, which regulates adipose tissue triglyceride metabolism) and Acsm5 (Acyl-CoA synthetase medium chain family member 5). Corticosterone-mediated flattening of circadian rhythm also induced expression of the lipid uptake receptor CD36, and corticosteroneinduced obesity and lipid accumulation in BAT and VAT were partially abrogated in CD36-null mice (113).…”
Section: Glucocorticoids and Bat Thermogenesismentioning
confidence: 94%
“…Intriguingly, two recent studies in mice implanted with corticosterone pellets have independently concluded that glucocorticoids stimulate BAT whitening by disrupting circadian rhythms related to lipid uptake (112,113). The uptake of triglyceride-derived fatty acids into BAT displays a circadian rhythm in mice: it is highest in the evening (when endogenous glucocorticoids are elevated), and this pattern was disrupted within a few days of pellet implantation (112,113). Lipid uptake was not perturbed by daily injections of corticosterone in the evening, however, suggesting that continuous elevation of corticosterone levels is required for BAT whitening.…”
Section: Glucocorticoids and Bat Thermogenesismentioning
confidence: 99%
“…GCs promote adipocyte differentiation ( 68-70 ). Dampened GC rhythms result in increased lipid accumulation and body weight gain due to upregulation of the FA transporter Cd36 ( 71 ). Hypercortisolemia increases lipolysis while at the same time promoting visceral adiposity, probably by enhanced preadipocyte differentiation ( 69 , 72 ).…”
Section: Oscillating Signals Regulate White Adipose Tissue Metabolismmentioning
confidence: 99%